Fermented soy whey induced changes on intestinal microbiota and metabolic inﬂuence in mice - Wei Han; Xuhui Zhuang; Qian Liu; Bo Sun; Haijiang Miao; Xiaolin Zhang (Food Science and Human Wellness)
Soy whey (SW) is generated as process waste while preparing soy protein isolates (SPI), and causing severe environmental pollution. Therefore, its value-added utilization is of prime importance for transforming and upgrading traditional industry. This study aims to utilize SW as a substrate for the growth of probiotics and produce a SW based synbiotics. By a series of trials, the effect of the dietary supplementation with this fermented SW (FSW) was analyzed on ICR mice's body weight, metabolites, and intestinal microbiota in 4 weeks. The results showed that, when SW was concentrated 15 times, the count of viable Lactobacillus casei reached 3.4 × 109 CFU/mL by liquid fermentation method, which was the highest viable cell count among all test strains. In this FSW, the protein, amino acid, total dietary fibre, soluble dietary fibre, and oligosaccharide were 2.10%, 1.63%, 0.52%, 0.51% and 0.79%, respectively. Compared to two control group, the total yields of the short chain fatty acids (SCFAs) were significantly improved (75%–125% at average), while the SCFAs structure was also significantly changed (especially acetic acid and butyrate) in the faeces of mice fed FSW. Meanwhile, FSW dietary addition was associated with the diversity and richness of the intestinal microbiota. Obviously, with mice's body weight loss, Firmicutes/Bacteroides ratio reduced accordingly (< 1.21), and the abundance of Akkermansia muciniphila was significantly increased (the maximum amount was about 0.013%). In summary, our results indicated that the dietary supplementation of FSW affected mice's intestinal microbiota and metabolism and improved their health profile.